2012
DOI: 10.1021/jp3069317
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Model for CO Adsorption and Dissociation on Clean and K-Doped β-Mo2C Surfaces

Abstract: We studied the effect of K on the adsorption and dissociation of CO on the β-Mo2C (001) surface by density functional theory calculations. Molecular CO adsorbs more strongly on Mo-terminated surfaces than on C-terminated ones. Adsorption is energetically more favorable in the presence of preadsorbed potassium. The CO molecule withdraws electron density from the surface, being more extended on the K-doped surface. The CO dissociation was also evaluated, and reaction pathways were modeled, revealing that the C-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…In addition to the lower activation barrier for CO 2 dissociation over K-promoted b-Mo 2 C(001), the higher CO selectivity and lower CO uptake of K-Mo 2 C/g-Al 2 O 3 (1.7 mmol g À1 )r elative to Mo 2 C/g-Al 2 O 3 (21.4 mmol g À1 )m ight indicate that addition of Kd ecreasest he CO bindinge nergy,a llowing CO to desorb beforei ti sf urther hydrogenated into CH 4 or other hydrocar- bons. However,D FT studies in the literature report that the addition of Kt oM o 2 Ci ncreases the binding energy and dissociation of CO. [31,39] Surface-science experiments by Bugyi et al using high-resolutione lectron energy loss spectroscopy (HREELS) and temperature-programmed desorption (TPD) also confirmed that the presence of Ko nM o 2 Cs urface increases the CO binding energy thereby promoting its dissociation. [40] Interestingly,o ur DFT calculations reveal that the desorption energy of CO from the surface with co-adsorbed O* from CO 2 dissociation (the final state in Figure6), seemst ob el ess sensitive to the presenceo fK .T he desorption energy of CO is almosti soenergetic for the K-promoted andp ure Mo 2 C(100) surfaces (51.2 and 51.0 kcal mol À1 ,r espectively (not shown)).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to the lower activation barrier for CO 2 dissociation over K-promoted b-Mo 2 C(001), the higher CO selectivity and lower CO uptake of K-Mo 2 C/g-Al 2 O 3 (1.7 mmol g À1 )r elative to Mo 2 C/g-Al 2 O 3 (21.4 mmol g À1 )m ight indicate that addition of Kd ecreasest he CO bindinge nergy,a llowing CO to desorb beforei ti sf urther hydrogenated into CH 4 or other hydrocar- bons. However,D FT studies in the literature report that the addition of Kt oM o 2 Ci ncreases the binding energy and dissociation of CO. [31,39] Surface-science experiments by Bugyi et al using high-resolutione lectron energy loss spectroscopy (HREELS) and temperature-programmed desorption (TPD) also confirmed that the presence of Ko nM o 2 Cs urface increases the CO binding energy thereby promoting its dissociation. [40] Interestingly,o ur DFT calculations reveal that the desorption energy of CO from the surface with co-adsorbed O* from CO 2 dissociation (the final state in Figure6), seemst ob el ess sensitive to the presenceo fK .T he desorption energy of CO is almosti soenergetic for the K-promoted andp ure Mo 2 C(100) surfaces (51.2 and 51.0 kcal mol À1 ,r espectively (not shown)).…”
Section: Resultsmentioning
confidence: 93%
“…In addition to the lower activation barrier for CO 2 dissociation over K‐promoted β‐Mo 2 C (001), the higher CO selectivity and lower CO uptake of K‐Mo 2 C/γ‐Al 2 O 3 (1.7 μmol g −1 ) relative to Mo 2 C/γ‐Al 2 O 3 (21.4 μmol g −1 ) might indicate that addition of K decreases the CO binding energy, allowing CO to desorb before it is further hydrogenated into CH 4 or other hydrocarbons. However, DFT studies in the literature report that the addition of K to Mo 2 C increases the binding energy and dissociation of CO . Surface‐science experiments by Bugyi et al.…”
Section: Resultsmentioning
confidence: 99%
“…The projector augmented wave (PAW) potentials [34] are used with a kinetic energy cutoff of 550 eV. PAW-PBE method has been shown to be very effective for cluster [35,36] and surface [37][38][39][40] approach was implemented in all calculations. A set of 9 × 9 × 1 Monkhorst-Pack grid [41] is used for Brillouin-zone (BZ) integration.…”
Section: Methods and Calculation Detailsmentioning
confidence: 99%
“…26 Furthermore, it has been predicted that d-MoC(001) can easily dissociate molecular oxygen 27 and DFT calculations showed the very high catalytic power of hexagonal a-Mo 2 C on ammonia dehydrogenation. 28 Also, hexagonal a-Mo 2 C(001) and orthorhombic b-Mo 2 C phases have been considered as catalysts for CO hydrogenation, [29][30][31] and very recently, b-Mo 2 C(001) has been proposed for CO dissociation.…”
Section: -16mentioning
confidence: 99%